CLUSTER ANALYSIS FOR BANK GROUPING BASED ON FINANCIAL STATEMENT - Widayanti, Asti; , Jamhur; Fadjar, Achmad (CENTRAL ASIA AND THE CAUCASUS, 2022)
Grouping the company especially bank was important to comparing banks performance. In Indonesia, the initial banking grouping was based on BUKU (Commercial Banks based on Business Activities) and currently a grouping has been developed according to KBMI (Bank Groups Based on Core Capital). The purpose of this study is to grouping bank in Indonesia based on financial statement performance using common size analysis, to find the financial statement structure for each cluster and compare the results of the grouping by clustering with the KBMI method. Grouping was done using the cluster method on the financial statements of bank in Indonesia. The variables used for this study are common size in the balance sheet and income statement. The number of banks in this study were 42 commercial banks listed on the Indonesia Stock Exchange with asset values above 1 trillion rupiah. Using financial report data in 2020, clustering is carried out into 4 groups according to the KBMI grouping. The results showed that there were 23 banks in cluster 1, 1 bank in cluster 2, 2 banks in cluster 3 and 16 banks in cluster 4. The characteristics for each cluster have different banking strategies in terms of credit policy, deposit value and capital value. Another characteristic is cost-to-profit performance. The grouping results are significantly different from the grouping based on KBMI, where not every bank with good core capital will have better performance.